2005
DOI: 10.1590/s0101-31222005000100001
|View full text |Cite
|
Sign up to set email alerts
|

Maturação fisiológica de sementes de sabiá

Abstract: O objetivo desta pesquisa foi estudar o processo de maturação de sementes de sabiá (Mimosa caesalpiniifolia Benth.). Foram realizadas dezesseis colheitas semanais de frutos e sementes de árvores, no município de Areia - Paraiba, no período de agosto a novembro de 2001. As colheitas iniciaram-se aos 105 dias e estenderam-se até os 210 dias após a antese. Foram avaliadas as dimensões, o teor de água e a massa fresca e seca de frutos e sementes, bem como a germinação e o vigor (primeira contagem de germinação, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
17

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 12 publications
1
11
0
17
Order By: Relevance
“…Similar results were obtained by Alves et al (2005), in which the fruits of Mimosa caesalpiniifolia reached maximum size values before the ripening point and decreased thereafter. Therefore it was not considered a good parameter to help…”
Section: Resultssupporting
confidence: 86%
“…Similar results were obtained by Alves et al (2005), in which the fruits of Mimosa caesalpiniifolia reached maximum size values before the ripening point and decreased thereafter. Therefore it was not considered a good parameter to help…”
Section: Resultssupporting
confidence: 86%
“…In seeds of the sabiá (Mimosa caesalpiniaefolia) (ALVES, 2003) and quaresmeira (Tibouchina granulose) (LOPES; DIAS; PEREIRA, 2005), the size of the fruit proved useful as a maturation index. In the same way, the physical differences seen in the length and diameter of the physalis fruit showed that classification using the colouration of the epidermis and calyx can be useful in assessing seed quality at different stages of maturation.…”
Section: Resultsmentioning
confidence: 99%
“…Seed dry weight when combined with other features was a good indicator of physiological maturity for Torresia acreana (Firmino et al, 1996), for Dalbergia nigra (Martins and Silva, 1997), for Cedrela fissilis (Corvello et al, 1999), for Cnidosculus phyllacanthus for Mimosa caesalpiniifolia by Alves (2005), for Peltophorum dubium by Aquino et al (2006), for Machaerium brasiliense by Guimarães and Barbosa (2007), and for Caesalpinia echinata by Aguiar et al (2007). However, for Barbosa et al (1992) fruit and seed dry biomass of Copaifera langsdorffii were not good indicators of physiological maturity.…”
Section: Resultsmentioning
confidence: 99%